Correlation of Soil Chemical, Biological, and Physical Characteristics on Productivity of Maize in Cibugel District, Sumedang Regency - Alifa Salsabila Anindya; Marenda Ishak Sonjaya Sule; Betty Natalie Fitriatin (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Maize as one of the national food commodities, experiences an increase in demand every year. Both internal and external factors influenced the growth of corn plants. Internal factors originated from the plant, such as inherited genetic traits, while external factors came from the environment, including soil properties and climate. External factors that affected plant growth included biological, physical, and chemical soil characteristics. This research aimed to understand the interrelation between soil acidity (pH), phosphorus availability (P), cation exchange capacity (CEC), nitrogen-fixing bacteria, earthworm population, carbon-nitrogen ratio (C/N), and soil texture on the productivity of maize in Cibugel District and how these factors were interconnected to support plant growth. The research employed a descriptive survey and comparative method, with soil samples taken from 18 soil samples from six villages in the Cibugel Subdistrict, Sumedang Regency. The correlation analysis results showed a significant positive relationship between cation exchange capacity and corn productivity and a significant negative relationship between available phosphorus and corn productivity. This implied that increasing cation exchange capacity could enhance productivity while increasing available phosphorus could decrease productivity. The research aided in identifying soil characteristics influencing high land productivity in the area.Â